The Influence of Entrepreneurial Leadership, Dynamic Capability, Innovation, and Digitalization on the Performance of MSME - Simanjuntak, Riski Hamonangan; Pasaribu, Manerep (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
The role of Micro, Small and Medium Enterprises (MSMEs) in a country's economy is very important. As one of the developing countries, the role of MSMEs in the Indonesian economy is very central, MSMEs are the largest contributor to GDP for Indonesia. However, MSMEs in Indonesia face problems related to low productivity. For this reason, this study tries to analyze the variables that drive MSME business performance. This research will examine how entrepreneurial leadership can drive dynamic capabilities, organizational innovation and digitization in MSMEs, in the end these factors will drive MSME business performance. This research will use the Structural Equation Modeling (SEM) method with the Partial Least Square (PLS). This study uses data from 168 MSME owners/managers in the food and beverage sector in Indonesia. The results of this study indicate that entrepreneurial leadership influences business performance through organizational innovation. Meanwhile, dynamic capabilities and digitization are not proven to be able to drive MSME business performance.